ON THE POSSIBILITY OF A SECOND KIND OF MANTLE PLUME - Cserepes L.; Yuen D.A. (My University, 2000)
Results from recent tomographic imaging of the mantle have revealed plume-like structures under some hotspots and renewed the interest in the theoretically possible forms of ascending jets in mantle convection. It is now a classical view that plumes reaching the lithosphere from below can, in principle, develop from boundary layers either at 660 km or at 2900 km depth. If both types are present in the mantle, the 660 km boundary layer, possibly due to the endothermic spinel-perovskite phase transition, must be partially penetrable. The present study shows that, with a partially penetrable phase boundary at 660 km depth, a further kind of plumes can develop, namely from below the 660 km boundary layer. These 'mid-mantle plumes' have no root in the deep lower mantle. If, as recent viscosity inversions suggest, a second low viscosity zone exists under the 660 km discontinuity, then this 'second asthenosphere' represents a well-focused source volume for the mid-mantle plumes. These upwellings are the counterparts of avalanche-like downwellings crossing the phase boundary in an intermittent manner. The condition for the development of mid-mantle plumes is that the phase boundary acts as a strong, but not fully impenetrable barrier to vertical flow. In two- and three-dimensional numerical simulations using a compressible fluid in a Cartesian box, it has been found that the critical parameters of mantle convection (Rayleigh number, phase transition characteristics) closely meet this condition. Mid-mantle plumes develop with an eruptive vigor, much faster than the boundary layer plumes and can produce huge plume heads, exceeding 1000 km in radius. They can thus explain very extensive, episodic flood basalt volcanism on the surface. If mid-mantle plumes really exist, they can contribute to the explanation of the diversity of hotspot basalt isotopic signatures since they sample a geochemical reservoir distinct from the classical plume sources.
Keywords: MANTLE; CONVECTION; MANTLE PLUMES; NUMERICAL MODELS